Analisis Penentuan Harga Pokok Produksi Lipa Songke Menggunakan Metode Activity Based Costing dan Harga Pokok Penjualan Menggunakan Cost Plus Pricing - Rezi, Rose Vererial Gesela; Soma, Leksianus; Atsigah, Najwa; Wahyudi, Agus (Universitas Kristen Wira Wacana Sumba, 2023)
This study aims to determine the calculation of the cost of production using the Activity Based Costing (ABC) method and determine the selling price using the Cost Plus Pricing method of lipa songke weavers in Mata Wae Village. This research is a qualitative research. Sources of data using primary and secondary data collected through observation, interviews, and documentation. The results of this study indicate that there are differences in production costs calculated by weavers using simple calculations using Activity Based Costing and selling prices using the cost plus pricing method. The results of this study indicate that the cost of production calculated by the weavers for the entire product is Rp. 590,000 while the calculation using the Activity Based Costing (ABC) method for the whole product is Rp. 990,000. then in terms of determining the cost of goods sold if using the cost plus pricing method, it can be obtained that the cost of goods sold lipa songke in Mata Wae Village is Rp. Rp. 1,138,500.